Reflections on entrepreneurship education in Professional Education Centers (CEDUPs) in Santa Catarina based on teachers’ perceptions (PerCursos, 2026)
This article analyzes the teaching of entrepreneurship in Professional Education Centers (CEDUPs) in the state of Santa Catarina, based on the perceptions of teachers who teach entrepreneurship-related curricular components in Integrated High School and Professional Education programs. Drawing on specialized and critical literature on entrepreneurship in education and in dialogue with the concept of Integrated High School (Kuenzer, 2017; Ramos, 2023), the study investigates the growing inclusion of entrepreneurship in the Professional and Technological Education (EPT) curriculum, driven by public policies and partnerships with the business sector. The research adopts a qualitative and exploratory approach and uses an online semi-structured questionnaire administered to 19 CEDUP teachers. The data were subjected to content and descriptive analysis. The results reveal that teachers have a predominantly technical background (57.9% hold bachelor's degrees), precarious employment conditions (94.7% under temporary contracts), and limited experience in the area (63.2% with less than three years), which inclines them to adopt a predominantly business-oriented perspective on entrepreneurship. This hegemony results from the convergence of multiple determinants: instrumental technical training, precarious teaching conditions, the institutionalized insertion of neoliberal policies, and weaknesses in critical pedagogical training. This convergence reinforces entrepreneurship as a neoliberal ideology that masks the structural contradictions of capitalism and transfers collective responsibilities to the individual, pointing to the need to problematize its centrality in curricula for the education of the working class.
Keywords: teaching entrepreneurship; professional education; integrated high school